Service and Voltage Sag Study of Humid and Dry Weather Utilities - Khan, Nasrullah; Marion, Norman; Bashi, Sinan Mahmod; Yusuf, Sallehhudin (Universiti Putra Malaysia Press, 2002)
This paper compares the voltage sag severity problems of two typical utilities operating in humid and dry hot environments. Based on power quality data and its analysis, it has been attempted to compare the quality of services to the customers of humid and dry weather terrains. To accomplish this study Tenaga asional Berhad (TNB) Malaysia and Water and Power Development Authority (WAPDA) Pakistan were chosen. Electrical distribution system fault histories of two utilities, leading to malfunctioning or indiscriminate operation of industrial process controlling computers, protective relays and AC type electromagnetic contactors thereby imposing costly shutdowns to quality conscious end users, were analyzed to establish the severity of voltage sag aggressiveness in both areas. Power quality reliability indices were calculated to measure the operational system performance. The study has been focused to formulate algorithm for estimating probability of nuisance trip outs in industrial organizations operating in humid and hot dry environments. Influence of poor power quality on industrial as well as utility protection and control equipment has been estimated from the field data spread over a few years. This power quality reliability study concludes that there are higher insulation levels for humid environments than the plain hot weathers. During this comparative power quality study project on the causes of voltage sags and steady state outages reliability indices, it was found that some 77% voltage sags were caused by short circuit faults on utility network, 11% due to inter facility faults but no cause could be assigned to remaining 14% voltage sags resulting in tripping of drives, draft fans, compressors PLCs, ammonia pumps, incinerators and process controllers. The reliability indices of humid utilities were found relatively poorer than its counterpart. The probability of severe voltage sags in humid environments was found to be much more than the dry hot weather terrain utilities.